2021
DOI: 10.5194/essd-13-777-2021
|View full text |Cite
|
Sign up to set email alerts
|

OceanSODA-ETHZ: a global gridded data set of the surface ocean carbonate system for seasonal to decadal studies of ocean acidification

Abstract: Abstract. Ocean acidification has profoundly altered the ocean's carbonate chemistry since preindustrial times, with potentially serious consequences for marine life. Yet, no long-term, global observation-based data set exists that allows us to study changes in ocean acidification for all carbonate system parameters over the last few decades. Here, we fill this gap and present a methodologically consistent global data set of all relevant surface ocean parameters, i.e., dissolved inorganic carbon (DIC), total a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
161
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(170 citation statements)
references
References 102 publications
9
161
0
Order By: Relevance
“…Further, numerical modeling study focusing on the coastal upwelling region of California Current System has also reported a similar pH range (7.85–8.20) (Hauri et al., 2013). Model derived pH records available for our study region (Gregor & Gruber, 2021) (Figure 5b) and for the north‐western Arabian Sea (Sreeush et al., 2019) are characterized by long‐term declining trend with much smaller pH variability. Whereas our δ 11 B coral derived pH record shows much larger pH variability with no discernable decreasing trend (Figure 5a) highlighting divergence between the proxy based reconstruction and numerical model simulations of the past pH.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Further, numerical modeling study focusing on the coastal upwelling region of California Current System has also reported a similar pH range (7.85–8.20) (Hauri et al., 2013). Model derived pH records available for our study region (Gregor & Gruber, 2021) (Figure 5b) and for the north‐western Arabian Sea (Sreeush et al., 2019) are characterized by long‐term declining trend with much smaller pH variability. Whereas our δ 11 B coral derived pH record shows much larger pH variability with no discernable decreasing trend (Figure 5a) highlighting divergence between the proxy based reconstruction and numerical model simulations of the past pH.…”
Section: Resultsmentioning
confidence: 84%
“…(a) The coral δ 11 B derived pH record from the Lakshadweep. (b) OceanSODA‐ETHZ model derived pH data extracted for 2° latitude × 2° longitude box centered at 8°N and 73°E (Gregor & Gruber, 2021). (c) Theoretical pH curves calculated using CO2sys program to understand how pCO 2 forcing and sea surface temperature contributed individually to pH changes near the study site during the studied time interval.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also benchmark the performance of ESM2M's saturation state of aragonite (Ω arag ) during the contemporary period against data-based estimates. Speci cally we assess ESM2M mean-state, anthropogenic trend and seasonal cycle relative to Ω arag derived from ETHZ-OceanSoda 43 , SOM-FFN 44 , JMA-MLR 45 and for the Southern Ocean, the Biogeochemical Southern Ocean State Estimate 46 (B-SOSE). Model validation is discussed more fully in Supplementary Discussion 1.…”
Section: Methodsmentioning
confidence: 99%
“…The SOOP-CO 2 provided pCO 2 data acquired from ships of opportunity 1 , while the growing BGC-Argo array (Claustre et al, 2020) will provide open ocean pH observations, in addition to salinity-derived TA. SOCAT (Bakker et al, 2016) and LDEO Global Surface Database (Takahashi et al, 2020) contribute to these international efforts by compiling quality CO 2 observations from the scientific community, while GLODAP (Lauvset et al, 2016) and OceanSODA-ETHZ (Gregor and Gruber, 2021) databases provide global gridded data of the open ocean carbonate system. The limited CO 2 system variability in the oceanic environment, compared to coastal ecosystems, favors observations of the alterations associated to climate change such as carbon accumulation or OA.…”
Section: Introductionmentioning
confidence: 99%